Objective Analysis of Circulation Extremes During the 21 July 2012 Torrential Rain in Beijing - 赵洋洋 张庆红 杜宇 江漫 张季平 (Acta meteorologica Sinica, 2013)
It has been reported that the heaviest rain event since 1951 hit Beijing on 21 July 2012 （henceforth referred to as the 721 case）.The frequency and extreme attributes of the large-scale circulation patterns observed during the 721 case are explored by using obliquely rotated T-mode principle component analysis （PCA） and reanalysis data from NCEP/NCAR.The occurrence frequency of the 721-type circulation during the summers of 1951-2012 is 10.9%,while the frequency of torrential rain under this type of circulation is 4.51%.Relative to other rainstorms with similar large-scale circulations during the study period,the 721 case is characterized by a more westward extension of the subtropical high over the western North Pacific,a stronger low-level jet in the lower troposphere over the south of Beijing,a larger amount of ambient precipitable water,and a stronger vertical wind shear over Beijing.Among the 621 days with the 721-type circulation during the study period,the 721 case ranks the 54th in terms of the 925-hPa low-level jet south of Beijing,the 209th in terms of the local vertical wind shear,and the 8th in terms of the local precipitable water.The 721 case is particularly extreme with respect to the 925-hPa low-level jet south of Beijing and local precipitable water.Cases with similar circulations and equal or greater values of the 925-hPa low-level jet south of Beijing and local precipitable water have occurred thrice during the summers of 1951-2012 （i.e.,once every 21 years）.